A Cross-National Study of Managerial Values - Bigoness, William J.; Blakely, Gerald L. (Journal of International Business Studies, 1996)
This study investigated cross-national differences in managerial values. A total of 567 managers from twelve nations participated in the study. Managerial values were assessed by means of Rokeach's value survey. Factor analysis of the eighteen instrumental values included in Rokeach's Value survey revealed four underlying value dimensions. The value dimension that included the instrumental values broadminded, capable and courageous was ranked as the most important value dimension by managers from all twelve nations. National differences were found on three of the four value dimensions.